Relationship Analysis of HNKPC and Monetary Policy on a NCM Framework in ASEAN-3 - Shella Elly Sritrisniawati; Evi Gravtiani; Guntur Riyanto (Universitas Negeri Semarang, 2022)
The Hybrid New Keynesian Philips Curve (HNKPC) is an update of the Philips Curve. HNKPC discusses the combination of forward looking and backward looking on the inflation rate. In this case, the shock of the inflation rate to the unemployment rate will be analyzed according to the HNKPC. The dynamics of inflation used from the monetary policy aspect is the inflation targeting framework (ITF). This research will also combine the inflation rate of various elements in the new consensus macroeconomic framework in ASEAN-3 as an up-to-date research idea. The object of analysis used is ASEAN-3 covering Indonesia, the Philippines and Thailand. The method used in this research is Structural Vactor Autoregression (SVAR) in the first quarter of 2000 – 4th quarter of 2021. The results of the SVAR find that inflation fluctuations are backward looking and forward looking in accordance with the HNKPC concept of the full unemployment rate in Indonesia, according to some in Thailand and not in the Philippines. The ITF is a monetary policy whose annual inflation target is determined by the central bank in accordance with the new consensus macroeconomic perspective